2021
DOI: 10.3390/ma14041052
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Cycling of (RE)BCO-Based Superconducting Tapes Joined by Lead-Free Solders

Abstract: We prepared overlap soldered joints of high-temperature superconducting tapes, using various materials and preparation conditions. In order to select the joints with optimal performance, we correlated their electrical properties (derived from current–voltage curves) with the microstructure of the respective joint cross-section by scanning electron microscopy. With the first group of joints, we focused on the effect of used materials on joint resistivity and critical current, and we found that the dominant role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Figure 4a shows the I c retention percentage versus specific resistance of the different furnace heating and resistive Joule heating samples. Most studies had suggested that a good joint required low specific resistance (<1 µΩ•cm 2 ) [27][28][29] and high I c retention percentage (>80%) [27], shown in Figure 4a with four clearly distinguished blocks. The first block indicates property of high specific resistance (>1 µΩ•cm 2 ) due to insufficient sintering of the nano-silver paste, and shows the obvious feature that some un-sintered nano-silver particle remains dark gray instead of white after the process, as shown in Figure 4b, which was observed in the test heated at 180 • C (furnace heating).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4a shows the I c retention percentage versus specific resistance of the different furnace heating and resistive Joule heating samples. Most studies had suggested that a good joint required low specific resistance (<1 µΩ•cm 2 ) [27][28][29] and high I c retention percentage (>80%) [27], shown in Figure 4a with four clearly distinguished blocks. The first block indicates property of high specific resistance (>1 µΩ•cm 2 ) due to insufficient sintering of the nano-silver paste, and shows the obvious feature that some un-sintered nano-silver particle remains dark gray instead of white after the process, as shown in Figure 4b, which was observed in the test heated at 180 • C (furnace heating).…”
Section: Discussionmentioning
confidence: 99%